From rivers to kidneys: bacteria found in drinking water and hemodialysis units in Brazil - Moura, Beatriz de Lima; Souza, Maria Izabela Doce Coelho de; Morais, Jonathan Soares Lima; Costa, Aurycéia Jaquelyne Guimarães da (Revista JRG de Estudos Acadêmicos, 2025)
Water is an essential resource for human survival and quality of life; however, it has also become a vehicle for the transmission of infectious diseases such as gastroenteritis, colitis, and bacterial dysentery, since in many Brazilian regions it is contaminated by pathogenic microorganisms. Therefore, water monitoring is crucial to ensure sanitary safety and the preservation of public health, as microbiological contamination has a direct impact on both individual and collective health, especially in places with high water circulation, such as hospitals and schools. In order to assess the quality of water intended for human consumption in Brazilian regions, this study aimed to compile previous scientific data on water quality to identify the main bacterial species found in samples of drinking water consumed by the Brazilian population. It also sought to highlight the main sources of water supply, including households, schools, and hospitals, and to discuss the environmental, social, sanitary, and public management risks associated with such consumption. A literature review was conducted using databases such as PubMed, Web of Science, Virtual Health Library (BVS), Google Scholar, and university repositories. In total, 53 articles were selected for analysis. Among the bacterial groups most frequently identified, total coliforms (23.6%) and fecal coliforms (10.5%) were the most prevalent. Regarding the species identified, whether through culture or molecular methods, Escherichia coli stood out, accounting for 16.8% of the total number of pathogenic microorganisms found to be non-compliant with microbiological safety standards, followed by Pseudomonas aeruginosa, with an incidence of 8.2%. These bacteria were detected in 15 different sources of water for human consumption, including hospital drinking fountains, cisterns, rivers, springs, mineral water, wells, school taps, school drinking fountains, household taps, university drinking fountains, water tanks, clay filters, water spouts, water filters, and even water used in the hemodialysis process. In the latter case, bacteria such as Pseudomonas aeruginosa, Staphylococcus aureus, and Mycobacterium gordonae were detected in hemodialysis water samples. Furthermore, bacteria were found in both pre- and post-treatment water samples as well as in dialysate, and in some cases, the same species were simultaneously isolated from the water system and from patients’ blood, confirming the correlation between environmental contamination and infections associated with dialysis therapy. Overall, the available data indicate poor microbiological quality of the water consumed by the population, as the results fall below the potability standards recommended by the World Health Organization. This reinforces the need for continuous monitoring, technical training of water supply system operators, and ongoing inspection.